A novel and widespread class of ketosynthase is responsible for the head-to-head condensation of two acyl moieties in bacterial pyrone biosynthesis - Kresovic, Darko; Schempp, Florence; Cheikh-Ali, Zakaria; Bode, Helge B. (Beilstein Journal of Organic Chemistry, 2015)
The biosynthesis of photopyrones, novel quorum sensing signals in Photorhabdus, has been studied by heterologous expression of the photopyrone synthase PpyS catalyzing the head-to-head condensation of two acyl moieties. The biochemical mechanism of pyrone formation has been investigated by amino acid exchange and bioinformatic analysis. Additionally, the evolutionary origin of PpyS has been studied by phylogenetic analyses also revealing homologous enzymes in Pseudomonas sp. GM30 responsible for the biosynthesis of pseudopyronines including a novel derivative. Moreover this novel class of ketosynthases is only distantly related to other pyrone-forming enzymes identified in the biosynthesis of the potent antibiotics myxopyronin and corallopyronin.
Keywords: cell–cell communication; ketosynthase; photopyrones; pseudopyronines; quorum sensing